Klasyfikacja dynamiczno-przestrzenna europejskiej przestrzeni regionalnej ze względu na poziom GOW - Strahl, Danuta; Markowska, Małgorzata (Dynamic and Spatial Classification of European Regional Space with Regard to the Level of Knowledge Based Economy, 2008)
The article presents the dynamic and spatial classification of European regional space at NUTS2 level with regard to the level of knowledge based economy (KBE). KBE assessment refers to two economy sectors: industry and services. In order to assess the level of KBE development at regional level, the methods of hierarchical objects classification were applied including two aspects of internal diversification: spatial, considering lower level objects and the dynamics of changes in KBE level. The classification results facilitated the construction of the general KBE measure, accumulated in industry and in services, at the hierarchical object level i.e. country level, considering the dynamics of changes with reference to the assumed variables which illustrate KBE in regions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 443-453